(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Familial hypomagnesemia with secondary hypocalcemia (FHSH) is a rare genetic autosomal recessive disorder caused by mutations in the TRPM6 gene, which encodes for the receptor which serves as an active channel that transports Mg2+ and Ca2+ ions. It results in hypomagnesemia and secondary hypocalcemia. Typical symptoms begin in the neonatal period with seizures and tetany that are resistant to antiepileptic medications. This is a treatable condition, and the treatment involves magnesium and calcium supplementation. If left untreated, prolonged hypomagnesemia can lead to long-term disability. Here we report a case of a 50-day-old term female infant, born to non-consanguineous parents, who presented with recurrent generalized seizures starting at 40 days of age. Initial evaluation revealed severe hypocalcemia with persistent seizures despite calcium and antiepileptic therapy. Further workup showed marked hypomagnesemia with hyperphosphatemia. Seizures responded only after magnesium supplementation. Genetic testing confirmed a TRPM6 gene mutation, establishing the diagnosis of primary hypomagnesemia with secondary hypocalcemia. The patient achieved complete seizure control and normal milestones of development with appropriate magnesium replacement therapy. J Bangladesh Coll Phys Surg 2026; 44: 135-137